The moment of truth: Proust, Barthes, and the contingency of old age. Issue 3 (16th March 2018) - Barry, Elizabeth
ABSTRACT: In his Preface to the Life of Rancé, Roland Barthes raised a set of questions about how to write about old age. A decade and a half later, proposing a new start for himself as a writer, he takes as his model Marcel Proust, a writer who rehabilitates the idea of pity in relation to ageing, and makes an encounter with old age a final turning point in his novel. The current reading of Proust, using Barthes's thoughts on both old age and Proust as a frame, argues for a much more selectively compassionate treatment of old age than Barthes claims for Proust, and questions the place of old age in Proust's aesthetic and intellectual scheme. Adam Phillips has argued that Proust is, in opening himself to accidental encounters with the past, also more comfortable than other writers with the contingency of the future, and death's imperviousness to prediction and control. Ageing and the approach of death are starkly depicted in the final volume of Proust's work, it is true, but their effects are mitigated by the constants of hierarchy and privilege in Proust's fictional world, and the question of what their depiction is for remains moot.